Regioselective lipase acylation as a useful tool for separation and selective protection of β-D-Gal(1→4)-D-GlcNAc and β-D-Gal(1→3)-D-GlcNAc disaccharides - LA FERLA, BARBARA; Lay, L; Russo, G; Panza, L. (Tetrahedron: Asymmetry, 2000)
Supported lipase from Candida antarctica (Chirazyme®) was employed for a regioselective protection of the 2-azido derivatives 1 and 2, synthetic equivalents of β-D-Gal(1→3)-D-GlcNAc and β-D-Gal(1→4)-D-GlcNAc (N-acetyl lactosamine), respectively. The selectivity of the enzyme towards 1 and 2 was also exploited for an easy separation of the mixture of the two compounds obtained from a straightforward synthetic approach. Copyright (C) 2000 Elsevier Science Ltd.